2003
DOI: 10.1300/j052v23n01_02
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Activity Profiles of Selected Immigrant Older Adults in Canada

Abstract: In Canada, the population of older adults is becoming ethnically diverse. However, our understanding of the health behaviors including diet and physical activity among this group is limited. The purpose of this study is to examine the dietary and physical activity profiles, and the factors that influence these behaviors, among older immigrants. The sample included 54 participants (mean age = 68 +/- 6 years) from Cambodian, Latin-American, Vietnamese and Polish groups. Measures included background questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…To our knowledge few studies to date have analyzed PA modes among ethnic minorities or immigrant groups. One of these was a study conducted in a group of older Canadian adults consisting of mainly Vietnamese, Cambodian, Polish, and Latin-American immigrants [22]. In this study, walking was the most frequently reported PA among Latin Americans, followed by aerobics.…”
Section: Discussionmentioning
confidence: 87%
“…To our knowledge few studies to date have analyzed PA modes among ethnic minorities or immigrant groups. One of these was a study conducted in a group of older Canadian adults consisting of mainly Vietnamese, Cambodian, Polish, and Latin-American immigrants [22]. In this study, walking was the most frequently reported PA among Latin Americans, followed by aerobics.…”
Section: Discussionmentioning
confidence: 87%
“…In spite of this, long exposure to Canadian culture tends to be associated with an increased fat and sodium intake [23, 34]. One study involving older adult immigrants in London, Ontario found that continuance of traditional eating habits and consumption of special ethnic foods can increase the risk of poor nutrition, particularly sodium intake, which was found to be as high as 238–474 % of the daily recommended intake for some individuals [35]. Overall carbohydrate intake tended to be lower among immigrants [36].…”
Section: Resultsmentioning
confidence: 99%
“…Changes due to living environment, availability of foods, and lifestyle factors such as urbanization and language barriers have also been shown to impede the Punjabi women’s efforts to maintain their traditional dietary practices. Lack of time for food preparation and unavailability of traditional ingredients and equipment in Canada were also identified as barriers to maintaining a traditional diet [35]. Availability and affordability of traditional foods were reported as important barriers to healthy eating among older Punjabi men living in British Columbia who tended to prefer traditional dishes [42].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups experience different barriers and facilitators to food intake and further research is needed to differentiate these influences (Shatenstein et al 2003(Shatenstein et al , 2004. Older adult immigrants have been identified as at increased risk for inadequate diets (Johnson and Garcia 2003), but research in this area is sparse despite our multicultural society. Additionally, understanding the complex interaction between individual and collective determinants is needed to move forward with health promotion efforts (Payette and Shatenstein 2005).…”
Section: The Need For More Researchmentioning
confidence: 99%